Diabetic nephropathy unmasked in pregnancy: a case report - Jagadeesan, Nithya; Sudhager, Aishwarya; Seralathan, Goutham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Nephropathy complicates 5-10% of pregnancies in women with diabetes and is associated with adverse maternal and fetal outcome. Degree of renal impairment and proteinuria in early pregnancy predicts pregnancy outcome. Diabetes presenting as nephropathy at diagnosis is less frequent. We report a case of biopsy proven diabetic nephropathy that was diagnosed during second trimester of pregnancy when she presented with early onset preeclampsia with nephrotic range proteinuria, moderate anemia. Anti hypertensives and insulin were titrated. She was on strict antepartum fetal surveillance. She had periodic follow up with nephrologist. Caesarean section was performed at 33 weeks because of imminent eclampsia with transverse lie. Postoperative recovery was uneventful. Control of hypertension is cornerstone in the management as this delays the progression of the disease.